CORRELATION OF SOME TRAITS IN OFFSPRING WHEN MATING KARAKOL SHEEP IN DIFFERENT VARIANTS ACCORDING TO THE PATTERN OF FLOWER ARRANGEMENT - Norboyeva G.S.; Gaziyev A. (Modern American Journals, 2025)
Studying the intercorrelation of important selection traits in generations when mating Karakul sheep in different variants according to the arrangement of flowers.
Keywords: Karakul sheep, lambs, homogenous and heterogenous mating, forms of offspring, picture of location of flowers, length, wool fiber length, durability of flowers, wool-fiber quality.